2017
DOI: 10.1016/j.ijid.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic therapy duration for prosthetic joint infections treated by Debridement and Implant Retention (DAIR): Similar long-term remission for 6 weeks as compared to 12 weeks

Abstract: In patients undergoing DAIR for hip or knee PJI, the likelihood of long-term remission was not significantly different for those receiving 6 versus 12 weeks of antibiotic therapy. Prospective randomized trials are required to confirm this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 27 publications
1
56
0
Order By: Relevance
“…The primary outcome is remission at the last follow-up, but the RCT can be adjusted for different important variables, such as the number of surgical debridements, the use of a negative pressure therapy, administration of a parenteral antibiotic regimen, or the total duration of antibiotic therapy. As in many fields of septic orthopedic surgery, the number of surgical debridements does not formally influence remission rates, which has been shown for chronic osteomyelitis [10], septic native joint arthritis [11], fracture device infections [12], infected open fractures [11], or prosthetic joint infections [13]. There is very little evidence to guide surgical treatment of patients who require a single versus multiple debridements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome is remission at the last follow-up, but the RCT can be adjusted for different important variables, such as the number of surgical debridements, the use of a negative pressure therapy, administration of a parenteral antibiotic regimen, or the total duration of antibiotic therapy. As in many fields of septic orthopedic surgery, the number of surgical debridements does not formally influence remission rates, which has been shown for chronic osteomyelitis [10], septic native joint arthritis [11], fracture device infections [12], infected open fractures [11], or prosthetic joint infections [13]. There is very little evidence to guide surgical treatment of patients who require a single versus multiple debridements.…”
Section: Discussionmentioning
confidence: 99%
“…[23], and Actinomyces or fungi [24]. To cite recent and our own examples of investigations regarding the overall antibiotic duration, sacral osteomyelitis [25], long-bone osteomyelitis [10], fracture device-related infections [12], spondylodiscitis [25], prosthetic joint infections [13], diabetic foot osteomyelitis [26,27], and many more failed to enhance remission rates if antibiotics were prolonged beyond 4-6 weeks, even in the presence of an infected implant. These emerging and relatively short durations are equally acknowledged by international consensus meetings [28] of surgeons and infectious disease physicians who treat these infections and perform research on them.…”
Section: Discussionmentioning
confidence: 99%
“…As in many field of septic orthopedic surgery, the number of surgical debridement does not formally influence remission rates, which has been shown for chronic osteomyelitis [10], septic native joint arthritis [11], fracture device infections [12], infected open fractures [11], or prosthetic joint infections [14]. There is very little evidence to guide surgical treatment of patients who require a single versus multiple debridements.…”
Section: Discussionmentioning
confidence: 99%
“…One primary focus currently for oral antibiotic use after DAIR is the duration of therapy. Although IDSA recommends 6 months, some studies such as Chaussade et al 70 have shown that antimicrobial therapy can be reduced to 6 to 12 weeks for specific microorganisms after DAIR due to the high oral bioavailability of drugs such as fluoroquinolones and rifampin. Additionally, they showed similar results to the OVIVA trial, 20 that IV antibiotics had similar rates of infection remission as oral antibiotics.…”
Section: Prophylactic Oral Antibiotics After Outpatient Primary Tkamentioning
confidence: 99%